Reshaping of soil carbon and nitrogen contents in quincentenary ancient rice terraces: The role of both short-term abandonment and prokaryotic functional groups - Li, Wenqing; Li, Zhongwu; Liu, Yaojun; Nie, Xiaodong; Deng, Chuxiong; Zhang, Guangye; Wang, Shuyuan; Xiao, Tao; Zheng, Han (Frontiers in Microbiology, 2022)
Microbial communities and function play an important role in soil carbon and nitrogen transformation, and terraces abandonment is prevalent in recent decades in the hilly areas of China. However, it is not clear about the alteration of soil carbon and nitrogen content and their associated prokaryotic communities after ancient rice terraces abandonment. Soil profile of 0–120 cm was excavated on dry land, forest land (both converted from ancient rice terraces abandonment), and ancient rice terraces. FAPROTAX database was used to predict the prokaryotic functional groups. The results showed that soil organic carbon (SOC) and total nitrogen (TN) content of ancient rice terraces abandoned into dry land (51.09%; 33.20%) and forest land (31.76%; 16.59%) were significantly reduced. Soil prokaryotic diversity and community composition changed dramatically after terraces abandonment, mainly affected by pH and ammonia nitrogen (NH4+–N). Community composition was more similar in dry land and forest land. Moreover, the functional genes abundance of bacterial community carbon (57.01%; 50.80%) and nitrogen (15.25%; 22.36%) transformation were significantly reduced in dry land and forest land, and the archaeal community decreased sharply in carbon transformation (28.10%; 46.50%). The results indicate that ancient rice terraces short-term abandonment reduced soil carbon and nitrogen content, which may be closely related to the decline of prokaryotic community functional groups. The prevalence of short-term rice terraces abandonment may pose adverse ecological risks in the hilly areas of China.